THE FAILURE OF SETTLEMENT OF HUMAN RIGHTS VIOLATIONS IN INDONESIA AND ITS SOLUTIONS - Patra, Rommy (Faculty of Law, Universitas Sebelas Maret, 2018)
Efforts to resolve human rights violations in Indonesia have been failed. It raises the question of the cause of the failure and the solution that must be taken to overcome it. The factors causing the failure of the settlement of human rights violations: (1) weak substance of legislation, especially Law number 26 Of 2000 on the Human Rights Court; (2) issues of authority and institutional relationships that are not synergistic especially between Komnas HAM and the Attorney General; (3) weak political will from the Government. The solution offered in overcoming the failure of the completion of human rights violations: (1) improve the substantial weaknesses in Law number 26 Of 2000 on the Human Rights Court by replacing it through the establishment of a new Act on Human Rights Court; (2) to organize institutional relations between Komnas HAM and the Attorney General in order to be synergistic in handling cases of human rights violations; (3) to re-establish the Truth and Reconciliation Commission (KKR); (4) The ruling government must have strong political will to resolve various cases of human rights violations with the support of civil society groups.